(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Companies operating in contemporary business environments are addressed to corporate social responsibility, which requires companies to provide stakeholders with both financial and non-financial information, adequately and continuously. Various international institutions have created numerous models of information disclosure for socially responsible companies about economic, environmental and social aspects of the business. Social performance indicators show the relationship of an organization with its stakeholders. These indicators have become the key indicators of non-financial performance of companies in recent years, but they are also used to assess management competencies and to support the risk management process within the company. Assessment of the scope and quality of social performance indicators disclosure is reviewed in this paper by structuring of the Social Disclosure Index, calculated by taking into account following indicators: qualification, gender and age structure, number of employees, termination of employment, volunteer activities, training of employees, support for employees, internal and external communication capabilities, injuries and lost work days due to injuries. The research includes 17 real sector companies included in the BELEXline Index in the period 2014-2018. The results indicate relatively low level of social performance indicators disclosure which are a) mainly revealing information contributing to greater visibility of the companies in the market, b) neutral from the standpoint of influencing the values presented in the financial statements.